Posttreatment of 3D‐printed surfaces for electrochemical applications: A critical review on proposed protocols - Diego P. Rocha; Raquel G. Rocha; Sílvia V. F. Castro; Magno A. G. Trindade; Rodrigo A. A. Munoz; Eduardo M. Richter; Lucio Angnes (Electrochemical Science Advances, 2022)
Abstract This mini‐review presents an overview of recent trends for 3D printed sensors and biosensors (with a focus on Fused Deposition Modeling (FDM) based technology), along with their posttreatment surfaces to improve electrochemical applications. The protocols described in the literature and advances in this field were covered, bringing a critical discussion about the achievements and limitations to improve the electrical properties of conducting filaments, as well as their electroanalytical performance. In addition, the pros and cons of the processes used in surface posttreatment to improve the performance of electrodes constructed by FDM are presented, comparing the time consumed during chemical and electrochemical treatments or combining the two to improve the characteristics of the sensors. Finally, the discussion about the real necessity of surface treatments of electrodes constructed by FDM technology, the techniques used for this, and some ecological protocols are discussed (surface posttreatments with and without reagents) or whether the simple optimization of printing parameters could also significantly improve the electrochemical performance of sensors built with such technologies.